Gums and stabilisers for the food industry 11 : [the proceedings of the Eleventh Gums and Stabilisers for the Food Industry Conference-Crossing Boundaries held on 2-6 July 2001 at The North East Wales Institute, Wrexham, UK] /: [the proceedings of the Eleventh Gums and Stabilisers for the Food Industry Conference-Crossing Boundaries held on 2-6 July 2001 at The North East Wales Institute, Wrexham, UK]. (2002) - Unknown
No abstract available